Political risk and cost of equity: The mediating role of political connections - Pham, Anh Viet (Journal of Corporate Finance, 2019)
This paper studies the mediating role that political connections play in the relationship between cost of equity and political risk (i.e., partisan political conflict and economic policy uncertainty). The key channel is the information advantage firms achieve from connections to politicians. I show that, in the face of rising economic policy uncertainty, the financial reports of firms with strong political connections exhibit less-uncertain language than non-connected peers, consistent with superior information enabling connected firms to hedge against policy uncertainty. Consequently, connected firms' cost of equity is less sensitive to rising economic policy uncertainty. However, in the event of extreme partisan political conflict, the possibility of legislative gridlock and resulting loss of information advantage increases the exposure of connected firms. This manifests in heightened uncertainty expressed in financial disclosures and consequently cost of equity. Adding further support to the proposed information channel, these differential effects of partisan conflict and economic policy uncertainty are shown to concentrate in industries where firm success is highly dependent on government spending and policy.